Indole-3-carbaldehyde Semicarbazone Derivatives: Synthesis, Characterization, and Antibacterial Activities - Fernando Carrasco; Wilfredo Hernández; Oscar Chupayo; Celedonio M. Álvarez; Sandra Oramas-Royo; Evgenia Spodine; Carmen Tamariz-Angeles; Percy Olivera-Gonzales; Juan Z. Dávalos (Journal of Chemistry)
Four indole-3-carbaldehyde semicarbazone derivatives, 2-((5-bromo-1H-indol-3-yl)methylene)hydrazinecarboxamide (1), 2-((5-chloro-1H-indol-3-yl)methylene)hydrazinecarboxamide (2), 2-((5-methoxy-1H-indol-3-yl)methylene)hydrazinecarboxamide (3), and 2-((4-nitro-1H-indol-3-yl)methylene)hydrazinecarboxamide (4) were synthesized and characterized by ESI-MS and spectroscopic (FT-IR, 1H NMR, and 13C NMR) techniques. The two-dimensional NMR (in acetone-d6) spectral data revealed that the molecules 1 and 2 in solution are in the cisE isomeric form. This evidence is supported by DFT calculations at the B3LYP/6-311++G(d,p) level of theory where it was shown that the corresponding most stable conformers of the synthesized compounds have a cisE geometrical configuration, in both the gas and liquid (acetone and DMSO) phases. The in vitro antibacterial activity of compounds 1–4 was determined against Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Pseudomonas aeruginosa and Escherichia coli) bacteria. Among all the tested semicarbazones, 1 and 2 exhibited similar inhibitory activities against Staphylococcus aureus (MIC = 100 and 150 μg/mL, respectively) and Bacillus subtilis (MIC = 100 and 150 μg/mL, respectively). On the other hand, 3 and 4 were relatively less active against the tested bacterial strains compared with 1, 2, and tetracycline.